2005
DOI: 10.1177/1078390305284659
|View full text |Cite
|
Sign up to set email alerts
|

Falls in an Inpatient Geriatric Psychiatric Population

Abstract: BACKGROUND: Falls are a major health care concern for older adults in hospital settings. The incidence of falls on psychiatric units tends to be higher than that on general acute care hospital units, with estimated rates of 13.1 to 25 per 1,000 inpatient days compared to 3 to 5 per 1,000 inpatient days, respectively. OBJECTIVE: The purposes of this study were to quantify the number and types of falls and identify the associated risk factors relevant to a psychiatric inpatient setting. DESIGN: This was a descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 9 publications
3
65
2
1
Order By: Relevance
“…Our tool, named IPFRAT, comprises 11 items, and is easy to understand and use in a real setting. The 10 fall episodes observed during the study period confirm the data found in literature about the frequency and therefore the importance of the event (Blair, 2005;Kerzman et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our tool, named IPFRAT, comprises 11 items, and is easy to understand and use in a real setting. The 10 fall episodes observed during the study period confirm the data found in literature about the frequency and therefore the importance of the event (Blair, 2005;Kerzman et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…Incidence of falls in this population ranges from 13.1 to 25 per 1,000 patient bed days. (Blair, 2005) Despite these considerations, few papers are available on this topic; only in recent times, two scales have been published, which assess the risk of falls in the psychiatric population, the Edmonson Psychiatric Fall Risk Assessment Tool -(EPFRAT) and the Wilson-Sims Fall Risk Assessment Tool (WSFRAT). The first has better predictive values than generic scales, but has unsatisfactory sensitivity (0.63).…”
Section: Introductionmentioning
confidence: 99%
“…In 2010-11, 1.3 million patient days (or one in every 10 days spent in hospital) by a person aged 65 and older was directly attributable to an injurious fall. Fall rates for inpatient psychiatric services can be three to four times higher than rates in general hospitals [13].…”
Section: Introductionmentioning
confidence: 93%
“…The more medication taken by an older adult, the greater the risk of falls, and in some instances medication is associated with the highest frequency and severity of falls in an older adult mental health services [13]. High rates of poly-pharmacology have been reported in psychiatric hospitals [38].…”
Section: Medicationmentioning
confidence: 99%
See 1 more Smart Citation